Surface studies of environmental reactive species during exhibition or storage of ancient Ag‐based artefacts1. (12th March 2014) - Faraldi, F.; Angelini, E.; Mezzi, A.; Riccucci, C.; de Caro, T.; Di Carlo, G.; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> The role played by environmental species affecting the long‐term stability of archaeological Ag‐based artefacts during museum exhibition or storage has been studied by means of the combined use of selected area X‐ray photoelectron spectroscopy, X‐ray diffraction, optical microscopy and scanning electron microscopy + energy dispersive spectrometry. The presence of fine particulate and of aggressive compounds in the museum atmospheres has been investigated by means of an innovative testing methodology based on Ag‐based reference alloys. The procedure has been applied to different areas of some museums in the Mediterranean Basin in order to consider representative environmental conditions of storage and exhibition of Ag‐based artefacts. The case studies of the National Roman Museum in Rome, Italy and of the Egyptian Museum of Cairo, Egypt will be illustrated. Furthermore, the study has been performed as a function of the alloy chemical composition and of the position of the reference specimens. The results of the superficial, micro‐chemical and morphological characterisations of the reference alloys are related to degradation parameters of ancient silver artefacts, as the presence of sulfur dioxide and chloride ions. The chosen methodology can be recommended to investigate the environmental key factors to consider for a safe storage or exhibition of archaeological silver artefacts, ensuring them a long stable life from a chemical–physical point of view. Copyright © 2014 John Wiley & Sons, Ltd.